PSYCHOLOGICAL ADAPTATION OF FOOTBALL REFEREE TO MODERN REQUIREMENTS OF THE GAME - Gevorgyan, A. E. (Modern Psychology, 2025)
The article summarizes the results of about 10 years of research on the reliability of a football referee. In the course of many years of work, a comprehensive study of the individual psychological characteristics of the referee was carried out. The results of the study made it possible to identify important psychological components that ensure the reliability of a referee’s activity, as well as some structural and psychological features of the system of training judges. A comprehensive study of the activities of a football referee showed that psychological adaptation to modern requirements is possible, but requires the acquisition of new professional knowledge and psychological preparation. At the same time, world experience shows that refereeing in modern football cannot be error-free without technical intervention.